Scaling Invariance of Sports Sex Gap - Tang, Lu; Ding, Wenzheng; Liu, Chengyi (Frontiers in Physiology, 2020)
The controversy over the evolution of sex gap in sports stems from the reported that women’s performance will one day overtake men’s in the journal Nature. After debate, the recent studies suggest that the sports sex gap have been stable for a long time, due to insurmountable physiological differences. To find a mathematical model that accurately describes this stable gap, we analyze the best annual records of men and women in 25 events from 1992 to 2017, and find that power-law relationship could be acted as the best choice, with an R-squares as high as 0.999 (p≤0.001). Then, based on the power law model, we use the records of men in 2018 to predict the performance of women in that year and compare them with real records. The results show that the deviation rate of the predicted value is only about 2.08%. As a conclusion it could be said that there is a constant sex gap in sports, and the records of men and women evolve in parallel. This finding could serve as another quantitative rule in biology.